2021
DOI: 10.3389/fpsyg.2021.650206
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Manner of Information Presentation on Risky Choice

Abstract: We are constantly faced with decisive situations in which the options are not presented simultaneously. How the information of options is presented might influence the subsequent decision-making. For instance, presenting the information of options in an alternative- or dimension-wise manner may affect searching patterns and thus lead to different choices. In this study, the effects of this manner of information presentation on risky choice according to two experiments (Experiment 1, N = 45; Experiment 2, N = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…We found that the values of SMI in the bid task were significantly greater than those in the choice task, suggesting that more alternative-based information searches were shown in the bid task rather than the choice task. This result is consistent with the strategy compatibility hypothesis given that the deliberate strategy usually posits an alternative-based information search pattern, whereas the heuristic strategy posits an attribute-based information search pattern (Liu et al, 2021a , b ). Our findings suggest that the elicitations in preference reversal may also influence the information search direction and may deepen our understanding of the mechanisms that underlie time preference reversal.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that the values of SMI in the bid task were significantly greater than those in the choice task, suggesting that more alternative-based information searches were shown in the bid task rather than the choice task. This result is consistent with the strategy compatibility hypothesis given that the deliberate strategy usually posits an alternative-based information search pattern, whereas the heuristic strategy posits an attribute-based information search pattern (Liu et al, 2021a , b ). Our findings suggest that the elicitations in preference reversal may also influence the information search direction and may deepen our understanding of the mechanisms that underlie time preference reversal.…”
Section: Discussionsupporting
confidence: 85%
“…The third measure is the search measure index (SMI), which quantifies the degree to which the direction of a search is alternative- or attribute-based (Bockenholt and Hynan, 1994 ; Pachur et al, 2013 ; Su et al, 2013 ; Liu et al, 2021b ). The predominance of alternative-based transitions increases with an increasing SMI value (Su et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Second, the association between the eye-tracking measures and the decision-making in UG can also be explored. The eye-tracking measures can reflect rich information about the cognitive process during decision-making and are sensitive to the final choices (Liu et al, 2020(Liu et al, , 2021bZhou et al, 2021). To our knowledge, few studies have tested the predicting effect of eye-tracking measures on UG decisions.…”
Section: Eye-tracking Technique In Ugmentioning
confidence: 99%
“…In recent years, research on human decision-making has expanded from purely behaviorist approaches that focus on decision outcomes to include more cognitive approaches focusing on the decision process that occurs prior to the response (Glaholt and Reingold, 2011 ). Among the process-tracing methodologies, the eye-tracking technique has been successful in studying the complex cognitive activities involved in decision-making (Sui et al, 2020 ; Liu et al, 2021a , b ; Zhou et al, 2021 ). This technology allows decision-makers to freely investigate information while providing researchers a way to measure the information uptake process (Just and Carpenter, 1984 ; Ashby et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…It depends on the difference between the observed alternative-wise and attribute-wise saccades (Böckenholt and Hynan, 1994 ). This index is frequently used in research on eye movements in decision-making to assess the general search direction of information acquisition (Su et al, 2013 ; Liu et al, 2021b ; Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%